Emotional intelligence and competitiveness in teachers of emblematic educational institutions Tarma - Paredes Pérez, Marco Antonio (2025)
Objective. it was to determine the relationship between emotional intelligence and competitiveness in teachers of emblematic institutions of the province of Tarma, Methods. Quantitative approach, basic type, correlational level, the sample was intentional non-probabilistic and consisted of 120 directors and teachers from 02 institutions emblematic. Results. there is a significant relationship between emotional intelligence and teacher competitiveness, since the p-value found was 0 and the value of the Spearman correlation coefficient was 0.930. Conclusions. Emotional intelligence is a highly reliablepredictor of competitiveness and teaching capacity, therefore, permanent training programs must be implemented to strengthen such capacities within a framework of sustainability and educational progress.